Development of novel low-copy nuclear markers for Hieraciinae (Asteraceae) and their perspective for other tribes - Krak, Karol; Alvarez, Inés; Caklová, Petra; Costa, Andrea; Chrtek, Jindrich; Fehrer, Judith (American journal of botany, 2012)
PREMISE OF THE STUDY: The development of three low-copy nuclear markers for low taxonomic level phylogenies in Asteraceae with emphasis on the subtribe Hieraciinae is reported. METHODS AND RESULTS: Marker candidates were selected by comparing a Lactuca complementary DNA (cDNA) library with public DNA sequence databases. Interspecific variation and phylogenetic signal of the selected genes were investigated for diploid taxa from the subtribe Hieraciinae and compared to a reference phylogeny. Their ability to cross-amplify was assessed for other Asteraceae tribes. All three markers had higher variation (2.1-4.5 times) than the internal transcribed spacer (ITS) in Hieraciinae. Cross-amplification was successful in at least seven other tribes of the Asteraceae. Only three cases indicating the presence of paralogs or pseudogenes were detected. CONCLUSIONS: The results demonstrate the potential of these markers for phylogeny reconstruction in the Hieraciinae as well as in other Asteraceae tribes, especially for very closely related species.
Keywords: Gene Dosage; sekvence nukleotidů; Gene Library; Asteraceae; Genes, Plant; genová knihovna; Cell Nucleus; genetická variace; fylogeneze; výpočetní biologie; intergenová DNA; Sequence Analysis, DNA; genová dávka; Phylogeny; sekvenční analýza DNA; buněčné jádro; DNA Primers; chromozomy rostlin; Chromosomes, Plant; genetické markery; DNA rostlinná; DNA, Plant; pseudogeny; DNA, Intergenic; DNA primery; Diploidy; Pseudogenes; Base Sequence; rostlinné geny; Genetic Variation; diploidie; Genetic Markers; Computational Biology